PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF PADA MATERI PEMBUATAN CELANA ANAK - Dian Retnasari; Chytra Mahanani; Laila Nurul Himmah (Balai Besar Guru Penggerak Jawa Timur, 2023)
The learning process requires learning media in an effort to increase student motivation and competence. In children's fashion learning, the basic competence of making pants is considered quite difficult by students; this is shown by the results of unsatisfactory student competence and low learning motivation. So it is important to develop interactive multimedia to help students learn. This research aims to develop learning media and test their feasibility. The development method used is 4D, namely define, design, develop, and disseminate. The results of the feasibility assessment of learning media based on the opinions of material experts received a percentage of 89% and were included in the